2022
DOI: 10.3389/fsurg.2022.976318
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid surgery versus endovascular intervention for patients with chronic internal carotid artery occlusion: A single-center retrospective study

Abstract: ObjectiveChronic internal carotid artery occlusion (CICAO) can cause transient ischemic attack (TIA) and ischemic stroke. Carotid artery stenting (CAS) with embolic protection devices and hybrid surgery combining carotid endarterectomy and endovascular treatment are effective methods for carotid revascularization. The objective of this study was to evaluate and compare the effect and safety of the two surgical procedures.MethodsThis was a single-center retrospective study. In this study, 44 patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Thirteen studies reported the time and method of surgical follow-up for 246 patients. The shortest follow-up time was 4 months [16] after surgery, and the longest follow-up time was 49 months [21] after surgery. A total of 19 (7.7%) patients who were followed up reported recurrences of stenosis and 17 (6.9%) cases of reocclusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies reported the time and method of surgical follow-up for 246 patients. The shortest follow-up time was 4 months [16] after surgery, and the longest follow-up time was 49 months [21] after surgery. A total of 19 (7.7%) patients who were followed up reported recurrences of stenosis and 17 (6.9%) cases of reocclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Duplicate articles, title abstracts, and full texts were screened, and irrelevant articles, case reports, and letters were excluded. One study with carotid stent restenosis hybrid surgery recanalization was excluded, and 16 eligible studies were finally included [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (Fig. 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…The hybrid approach consists of endovascular stent angioplasty and carotid endarterectomy. In the study investigating the effect of hybrid and endovascular treatment of patients with chronic ICA occlusion 2 , the successful recanalization rate was 84.1% in patients with the hybrid surgery versus 51.4% in those with endovascular treatment. During the follow-up over 24 months, one patient died of a cardiovascular event, recurrent stroke took place in one unsuccessful patient, one patient had restenosis and one patient had reocclusion in the hybrid surgery group.…”
Section: Introductionmentioning
confidence: 99%